2007
DOI: 10.1111/j.1464-410x.2007.07161.x
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study on the early use of the vacuum erection device after radical retropubic prostatectomy

Abstract: OBJECTIVE To evaluate the effect of the early use of the vacuum erection device (VED) on erectile dysfunction (ED) and penile shortening after radical retropubic prostatectomy (RP), as these are important concerns for men choosing among treatment alternatives for localized prostate cancer. PATIENTS AND METHODS Twenty‐eight men undergoing RP were randomized to early intervention (1 month after RP, group 1) or a control group (6 months after RP, group 2) using a traditional VED protocol. An International Index o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
116
0
7

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(127 citation statements)
references
References 27 publications
3
116
0
7
Order By: Relevance
“…Studies as well as review articles on this topic that summarize research to date are available in this and other publications. 1,3,5,6,8,9,[11][12][13][14] In spite of the advances toward the restoration of erectile functioning promoted by nerve-sparing surgery, [15][16][17][18] penile rehabilitation 16,[19][20][21][22] and erectogenic aids, 3,11,[23][24][25] satisfaction with erectile dysfunction treatment appears to vary with the particular treatment, and is typically reported not to be high by the men who sought help. 13,26,27 Miller et al 28 reported that only 10% of men were satisfied with their treatments.…”
Section: Resultsmentioning
confidence: 99%
“…Studies as well as review articles on this topic that summarize research to date are available in this and other publications. 1,3,5,6,8,9,[11][12][13][14] In spite of the advances toward the restoration of erectile functioning promoted by nerve-sparing surgery, [15][16][17][18] penile rehabilitation 16,[19][20][21][22] and erectogenic aids, 3,11,[23][24][25] satisfaction with erectile dysfunction treatment appears to vary with the particular treatment, and is typically reported not to be high by the men who sought help. 13,26,27 Miller et al 28 reported that only 10% of men were satisfied with their treatments.…”
Section: Resultsmentioning
confidence: 99%
“…These findings support the rationale for not applying the constrictive ring when VCD is used for penile rehabilitation. 25 Köhler and coauthors 59 recently performed a pilot study on the early use of the VCD after RP. Twenty-eight men undergoing RP were randomized to early intervention (1 mo after surgery, group 1) or a control group (6 mo after surgery, group 2) using a traditional VCD.…”
Section: Vacuum Constriction Devicesmentioning
confidence: 99%
“…Köhler and colleagues 29 recently performed a pilot study on the early use of the vacuum constriction devices after RP. Twenty-eight men undergoing RP were randomized to early intervention (1 mo after surgery, group 1) or a control group (6 mo after surgery, group 2) using a traditional vacuum constriction device.…”
Section: Evidence In Support Of Penile Rehabilitationmentioning
confidence: 99%